Implementasi Kurikulum 2013 Melalui Analisis Buku Ajar PAI Kelas XI di SMA N I Balapulang - Ridlotun Nasikha (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
This study examines the content aspects of the grade XI Islamic Religious Education textbook in terms of the four core competencies of the 2013 curriculum, which include spiritual attitudes, social attitudes, knowledge and skills. Researchers chose SMA N 1 Balapulang in 2020/2021 as the object of implementation of the textbook. The type of research that will be used is field research. Data collection using observation, interview, and documentation methods. The analysis used is descriptive of textbooks and field objects as a place of implementation, namely at SMA N I Balapulang class XI. The results of this study indicate that the PAI textbook used is quite ethical, aesthetic, communicative and functional. In terms of writing, spelling, punctuation, vocabulary, sentences and paragraphs in accordance with the rules, terms used in the book and of course also easy to understand. This is also supported by adequate high school facilities, including teachers and students who can carry out 2013 Curriculum learning activities. In addition, it is also evidenced by the achievements made by SMA N 1 Balapulang which can compete with other favorite schools.